TINGKAT PERSAINGAN DAN EFISIENSI BANK PEMBIAYAAN RAKYAT SYARIAH DI INDONESIA - Afrianty, Nonie; Anto, Moh. Bekti Hendrie (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2017)
Abstract :  The development of sharia banking in Indonesia can not be separated from its important  role  as  an  intermediary  institution  as  well  as  developing  the economy by channeling  funds for productive businesses, especially middle, small and micro entrepreneurs. Sharia banking that has a strategic role in funding for micro business is one of them is the Sharia Rural Bank (BPRS). Therefore, BPRS must operate efficiently to promote economic growth and competitiveness so as to survive in the face of tight financial industry competition in Indonesia. This research is conducted to analyze the level of competition / competition and efficiency of Sharia Rural Bank (BPRS) in Indonesia. The data used in this research is the financial report of 113 BPRS in Indonesia obtained from Bank Indonesia. The methods used to analyze the level of competition are Herfindahl-Hirschman Index (HHI) and Concentration Ratio (CR). The analysis of this level of competition includes three variables, including assets, Third Party Funds (DPK) and Financing. While the methods used to analyze the level of efficiency include two input variables and three output variables,  including  DPK,  Operational  Costs,  Financing  Disbursed, Current  Assets  and  Other  Operating  Income.Analisis  of  BPRS competition level in Indonesia in 2011-2015 shows that BPRS in Indonesia tend to experience competition or competition between BPRS and not controlled by several BPRS. While at the level of efficiency of BPRS in Indonesia 2011-2015 using Data Envelopment Analysis (DEA) approach resulted 5 (five) BPRS with efficiency value 1 or 100%. In addition, for SRBs in inefficient conditions the DEA method also provides a reference or reference in order to be able to achieve efficient conditions.Keywords: Competition,         HHI         and         CR,         Efficiency,         DEA,         SR